Impact of a stress management program on weight loss, mental health and lifestyle in adults with obesity: a randomized controlled trial - Xenaki, Niovi (J Mol Biochem, 2018)
Aim: To evaluate the impact of a stress management program on weight loss, depression, anxiety and stress as well as on the adoption of healthy lifestyle in adults with obesity. Methods: Adults with obesity who sought help for weight loss at a medical obesity clinic were consecutively enrolled in the study and were randomly assigned to the intervention or control group. All participants received standard instructions for a healthy lifestyle. The intervention group attended an 8-week stress management program that comprised diaphragmatic breathing, progressive muscle relaxation, guided visualization and instructions about healthy nutrition/dietary habits. Anthropometric parameters were assessed and several questionnaires were completed by all participants, at the beginning and at the end of the study. Results: A total of 45 adults (mean age±SD 45.7±10.55 years) with obesity were enrolled in the study; 22 in the intervention group and 23 in the control group. Participants in the two groups were matched for age and BMI. Participants in the intervention group achieved a significantly larger reduction in BMI compared to the control group (ΔBMI −3.1 vs. −1.74 kg/m(2) respectively, P<0.001). In addition, they displayed ameliorated depression and anxiety scores and a reduction in the health locus of control based on chance.